Penyerapan dan Pengubahsuaian Konsonan Arab dalam Bahasa Melayu - Ahmad, Zaharani; Osman, Maizura; Jalaluddin, Nor Hashimah (Jurnal Bahasa, 2011)
This article examines and explains the phonological behaviour of Arabic loanwords in Malay, particularly those that contain consonantal phonemes. Arabic consonants that are identical to their Malay counterparts are not an issue because they can be accepted by the native grammatical system. However, in cases where there is no segmental correspondence between the two languages, two types of phonological behaviour can be observed, namely (i) foreign consonants are imported and become part of Malay phonemic inventory, and (ii) foreign consonants are modified and substituted by the native consonants. The factors that determine whether a consonant undergoes importation or substitution are the manner of articulation and the place of articulation. If the manner and place of articulation involved in the production of the Arabic consonants are familiar to the Malay phonological system, then the consonant will be absorbed from the loan source. However, if the manner and place of articulations are alien to the Malay language, modifications need to take place. The processes of consonantal modification in the study are analysed by employing the theory of the autosegmental phonology of feature geometry. Three important rules that operate here are debuccallisation, depharyngealisation and the backing rule. These rules are formalised as a delinking of a autosegment from the feature representation of the consonantal phoneme.